2014
DOI: 10.1186/s12284-014-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene response in rice plants treated with continuous fog influenced by pH, was similar to that treated with biotic stress

Abstract: BackgroundThroughout Asia, including Japan, rice plants are cultivated in a wide range of areas from lowlands to highlands and are frequently exposed to fog, including acid fog. Some physiological studies have shown that acid fog can be a stress factor for plants. We analyzed the gene expression profiles of rice plants treated with artificially prepared simulated acid fog (SiAF) or simulated neutral fog (SiNF) for 1 or 7 days.ResultsMicroarray analysis results suggested that both the SiAF and the SiNF treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Cluster analysis revealed that rice cultivars responded differently to simulated acid rain. Satoh et al [23] suggested that simulated acid fog treatments induced the expression of genes involved in the defense and stress responses in rice plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster analysis revealed that rice cultivars responded differently to simulated acid rain. Satoh et al [23] suggested that simulated acid fog treatments induced the expression of genes involved in the defense and stress responses in rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated acid rain at pH < 1.5 caused changes in the metabolism of the antioxidative system of Georgia wheat species [26]. Satoh et al [23] revealed that simulated acid fog caused similar responses to biotic stresses and ozone stress. The apoplast genes encoding NADPH oxidase and germin were also induced by simulated acid fog and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the overall benefits will be the time and cost that are needed for completing the growth rate measurements. This is significant for enabling assessment of large germplasm for crop improvement [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%